Survival and risk of adverse events in older patients receiving postoperative adjuvant chemotherapy for resected stages II-IIIA lung cancer: observational cohort study. (14th July 2011) - Wisnivesky, Juan P; Smith, Cardinale B; Packer, Stuart; Strauss, Gary M; Lurslurchachai, Linda; Federman, Alex; Halm, Ethan A
Abstract : Objective To compare the survival and risk of serious adverse events in older patients with stages II-IIIA non-small cell lung cancer treated with or without postoperative platinum based chemotherapy. Design Observational cohort study. Setting Cases of lung cancer in Surveillance Epidemiology and End Results registry linked to Medicare files, 1992-2005, and follow-up data to December 2007. Participants 3324 patients aged more than 65 years with resected stages II-IIIA lung cancer. Main outcome measures Primary outcome was overall survival and secondary outcome was the rate of serious adverse events among older patients treated with or without adjuvant chemotherapy. Results Overall, 21% (n=684) of patients received platinum based chemotherapy. Analyses adjusted, stratified, or matched by propensity scores showed that chemotherapy was associated with improved survival (hazard ratio range 0.78-0.81). The beneficial effect of chemotherapy was also observed among patients treated with radiation therapy (0.75-0.77) or without radiation therapy (0.74-0.77); however, chemotherapy was not beneficial for patients aged 80 or more (1.32-1.46). Adjuvant chemotherapy was associated with an increased odds of serious adverse events (odds ratio 2.0, 95% confidence interval 1.5 to 2.6). Conclusions Platinum based adjuvant chemotherapy is associated with reduced mortality and increased risk of serious adverse events in older patients with stages II-IIIA lung cancer. The magnitude of the benefit is similar to that observed in randomised controlled trials carried out among selected patients.